Preparation method of oxychloride electrolyte material, material and all-solid-state battery
The oxychloride electrolyte material is prepared by reacting metal chloride and lithium hydroxide in an inert gas atmosphere, and the oxychlorine frame structure is used to reduce the lithium ion diffusion activation energy, which solves the problem of low ion conductivity of existing halide solid electrolytes at room temperature, and achieves high performance of all-solid-state batteries at room temperature.
Patent Information
- Application Number
- CN202411690999.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-11
AI Technical Summary
The existing halide solid electrolytes have low ionic conductivity at room temperature, making it difficult to meet the high performance needs of all-solid lithium batteries.
By reacting metal chloride and lithium hydroxide in an inert gas atmosphere, an oxychloride electrolyte material is prepared, and the lithium ion diffusion activation energy is reduced by using the oxychlorine frame structure, thereby improving the room temperature ion conductivity.
The high ionic conductivity of oxychloride electrolyte materials at room temperature is achieved, and the room temperature magnification performance of all solid state batteries is improved.
Smart Images

Figure CN119591155A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of all-solid-state batteries, and in particular to a preparation method of an oxychloride electrolyte material, the material, and an all-solid-state battery. Background Art
[0002] All-solid-state batteries, based on solid-state electrolytes, have attracted widespread attention as a new generation of energy storage devices. Solid-state electrolytes typically require high ionic conductivity, good electrode compatibility, and excellent mechanical properties to be considered ideal electrolytes for high-performance all-solid-state lithium batteries. Ionic conductivity is one of the most important evaluation factors for solid-state electrolytes. However, the ionic conductivity of halide solid electrolytes is inferior to that of other solid electrolytes. Currently prepared halide solid electrolytes only have high ionic conductivity at high temperatures, while the ionic conductivity at room temperature remains very low. Summary of the Invention
[0003] In view of the above problems, the object of the present invention is to provide a preparation method, material and all-solid-state battery of an oxychloride electrolyte material with high ionic conductivity at room temperature. The technical solution is as follows:
[0004] In one aspect, a method for preparing an oxychloride electrolyte material is provided, the method comprising:
[0005] Providing raw materials; the raw materials include metal chloride and lithium hydroxide;
[0006] Under an inert gas atmosphere, the metal chloride in the raw material reacts with the lithium hydroxide to obtain the oxychloride electrolyte material generated by the reaction.
[0007] In an exemplary embodiment, the metal chloride is one of NbCl5 or TaCl5.
[0008] In an exemplary embodiment, providing raw materials includes:
[0009] Under an inert gas atmosphere, the metal chloride and the lithium hydroxide are weighed in an equimolar ratio.
[0010] In an exemplary embodiment, before weighing the lithium hydroxide, the method further comprises:
[0011] The lithium hydroxide is pre-treated by vacuum drying to obtain weighed lithium hydroxide, wherein the moisture value of the weighed lithium hydroxide is less than 30 ppm.
[0012] In an exemplary embodiment, reacting the metal chloride in the raw material with the lithium hydroxide to obtain the oxychloride electrolyte material generated by the reaction includes:
[0013] The metal chloride in the raw material is reacted with the lithium hydroxide by ball milling to obtain the oxychloride electrolyte material generated by the reaction.
[0014] In an exemplary embodiment, the mass ratio of the ball milling balls to the raw material is (10-45):1.
[0015] In an exemplary embodiment, the ball milling speed is 200-300 rpm.
[0016] In an exemplary embodiment, the ball milling time is 10 to 60 hours.
[0017] On the other hand, the present invention further provides a material comprising the oxychloride electrolyte material prepared by any of the methods described above.
[0018] On the other hand, the present invention also provides an all-solid-state battery comprising a material as described above.
[0019] The present invention discloses a method for preparing an oxychloride electrolyte material, comprising: providing raw materials; the raw materials comprising metal chloride and lithium hydroxide; and reacting the metal chloride in the raw materials with lithium hydroxide under an inert gas atmosphere to obtain the oxychloride electrolyte material. By using lithium hydroxide as the lithium raw material, which is inexpensive, the preparation cost is reduced. During the reaction, hydrogen chloride is generated, providing an acidic catalytic environment and shortening the preparation time. The prepared oxychloride electrolyte material incorporates oxygen and chlorine elements. The oxychlorine framework structure formed by the oxygen and chlorine elements is a significantly flexible ionic framework structure, which reduces the activation energy for lithium ion diffusion, thereby improving the room temperature ionic conductivity of the oxychloride electrolyte material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] To more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the embodiments or descriptions of the prior art. Obviously, the drawings described below are only some embodiments of the present invention, and those skilled in the art can derive other drawings based on these drawings without inventive effort.
[0021] Figure 1 This is a flow chart of a method for preparing an oxychloride electrolyte material provided by an embodiment of the present invention;
[0022] Figure 2 This is a spatial structure diagram of LiNbOCI4 provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0023] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0024] With the increasing popularity of electric vehicles, all-solid-state lithium batteries (ALLSLBs) have become a promising option for the next generation of power sources due to their inherent characteristics of high safety and high energy / powder density. A key component of ALLSLBs is the solid electrolyte, whose advancements have dominated the development of ALLSLBs. Solid electrolytes typically require high ionic conductivity, good electrode compatibility, and good mechanical properties to be considered ideal electrolytes for high-performance ALLSLBs. One of the most important evaluation factors for solid electrolytes is ionic conductivity, which is closely related to the structure of the solid electrolyte material.
[0025] Over the past few decades, breakthroughs have been made in halide solid electrolytes with high lithium ion conductivity. The earliest research on halide solid electrolytes can be traced back to the 1930s. The halide solid electrolyte material LiAlCl4 was first reported in 1923, but its ionic conductivity was not reported until 1977. Since then, various Li2MCl4 and Li2MBr4 compounds (where M is a transition metal) have been developed to improve ionic conductivity. Unfortunately, these compounds can only have high ionic conductivity at high temperatures, while the ionic conductivity at room temperature is still very low.
[0026] Therefore, it is very necessary to develop a method to prepare halide solid electrolytes with high ionic conductivity at room temperature.
[0027] This application embodiment provides a method for preparing an oxychloride electrolyte material. Figure 1 , Figure 1 The present invention is a flow chart of a method for preparing an oxychloride electrolyte material, the method comprising the following steps:
[0028] Step S1 includes: providing raw materials; the raw materials include metal chloride and lithium hydroxide.
[0029] Step S2 includes: reacting the metal chloride in the raw material with lithium hydroxide under an inert gas atmosphere to obtain an oxychloride electrolyte material generated by the reaction.
[0030] Specifically, lithium hydroxide is used as the lithium raw material, which is inexpensive and reduces preparation costs. The reaction with the metal chloride generates hydrogen chloride, which provides an acidic catalytic environment, accelerates the reaction, and shortens the reaction time. The resulting oxychloride electrolyte material incorporates oxygen and chlorine. The oxychlorine framework structure formed by these elements is a distinctly flexible ionic framework, which reduces the activation energy for lithium ion diffusion, thereby improving the room-temperature ionic conductivity of the oxychloride electrolyte material. Argon or nitrogen can generally be used as the inert gas, and the specific choice can be based on actual needs.
[0031] In the embodiment of the present application, the metal chloride is one of NbCl5 or TaCl5.
[0032] Specifically, metal chloride NbCl5 or TaCl5 is used as a raw material, and metal elements and chlorine elements are introduced. Both Nb metal elements and Ta metal elements have a body-centered cubic structure. For example, NbCl5 is used as a raw material to react with lithium hydroxide to prepare an oxychloride electrolyte material LiNbOCI4. Its spatial structure can be seen in Figure 2 , the crystal of LiNbOCI4 contains [NbOCI4] - The structure is composed of molecular chains, which are NbO2CI4 octahedra formed by bridging oxygen atoms, resulting in multiple partially occupied isoenergetic lithium sites in the lattice tending to be stable. These sites will [NbOCI4] - The chains are loosely bound together and reinforced by weak CI-CI van der Waals forces between the chains. The highly disordered lithium ion sites coupled with the obvious flexibility of the oxychlorinated framework lead to a lower activation energy for lithium ion diffusion and improved room-temperature ionic conductivity of lithium ions.
[0033] In the embodiment of the present application, providing the raw materials includes: weighing metal chloride and lithium hydroxide in an equimolar ratio under an inert gas atmosphere.
[0034] Specifically, the moisture and oxygen contents in the inert gas atmosphere are both less than 0.1 ppm, and contact between lithium hydroxide and oxygen and water is avoided as much as possible, thereby ensuring the purity of lithium hydroxide and the reaction effect.
[0035] In the embodiment of the present application, before weighing lithium hydroxide, the following steps are also included:
[0036] The lithium hydroxide is pre-treated by vacuum drying to obtain weighed lithium hydroxide, and the moisture value of the weighed lithium hydroxide is <30ppm.
[0037] Specifically, the present application considers that the lithium hydroxide raw materials purchased on the market are LiOH and LiOH .H2O, the moisture content of these two types of lithium hydroxide generally does not meet the requirement of <30ppm, which affects the performance of the oxychloride electrolyte material generated by the reaction. Therefore, the LiOH or LiOH purchased on the market . H2O needs to be vacuum dried before weighing to ensure that the moisture content of the weighed lithium hydroxide is less than 30ppm. . H2O is used as the raw material for lithium hydroxide to be vacuum dried and pre-treated, and tested with a moisture meter to ensure that the moisture value of lithium hydroxide is <30ppm, and then weighed and added. . The price of H2O is low, which reduces the preparation cost of the oxychloride electrolyte material.
[0038] In the embodiment of the present application, the metal chloride in the raw material reacts with lithium hydroxide to obtain an oxychloride electrolyte material comprising:
[0039] The metal chloride in the raw material is reacted with lithium hydroxide by ball milling to obtain an oxychloride electrolyte material generated by the reaction.
[0040] Specifically, by ball milling, the metal chloride and lithium hydroxide can be efficiently reacted at room temperature to obtain an oxychloride electrolyte material.
[0041] In the embodiment of the present application, the mass ratio of the ball milling balls to the raw materials is (10-45):1.
[0042] Specifically, the ball milling efficiency is improved by adjusting the mass ratio of the ball milling balls and the raw materials, so as to obtain the oxychloride electrolyte material with the target particle size.
[0043] In the embodiment of the present application, the rotation speed of the ball mill is 200-300 rpm.
[0044] Specifically, the ball milling efficiency is improved by adjusting the rotation speed of the ball mill.
[0045] In the embodiment of the present application, the ball milling time is 10 to 60 hours.
[0046] Specifically, the ball milling time is adjusted to improve the reaction effect of the ball milling reaction.
[0047] The embodiments of the present application also provide a material comprising an oxychloride electrolyte material prepared by any of the methods disclosed in the embodiments of the present application.
[0048] Specifically, the embodiment of the present application provides raw materials, which include metal chloride and lithium hydroxide, and the metal chloride is one of NbCl5 or TaCl5. Under an inert gas atmosphere, the metal chloride and lithium hydroxide are weighed in an equimolar ratio. Before weighing the lithium hydroxide, the previous lithium hydroxide is vacuum dried and pretreated to obtain weighed lithium hydroxide, and the moisture value of the weighed lithium hydroxide is <30ppm; under an inert gas atmosphere, the metal chloride and lithium hydroxide in the raw materials are reacted by ball milling to obtain an oxychloride electrolyte material generated by the reaction; wherein the mass ratio of ball milling balls to raw materials is (10~45):1, the ball milling speed is 200~300rpm, and the ball milling time is 10~60h.
[0049] In addition, when the metal chloride raw material is TaCl5, it is ball-milled with lithium hydroxide to obtain an oxychloride electrolyte material, and the oxychloride electrolyte material can be further heat-treated, wherein the heat treatment temperature is 150-350°C and the heat treatment time is 0.5-2h to obtain the final oxychloride electrolyte material, further improving its room temperature ionic conductivity.
[0050] The embodiments of the present application also provide an all-solid-state battery, comprising any one of the materials disclosed in the embodiments of the present application.
[0051] Specifically, the all-solid-state battery of the embodiments of the present application includes any one of the materials disclosed in the embodiments of the present application.
[0052] The present invention has no special requirements for the preparation of the battery, and the conventional preparation method of the all-solid-state lithium battery in the art can be adopted. The specific preparation process is well known in the field of solid-state batteries and will not be described in detail here.
[0053] The technical solution of this application is described below with reference to specific embodiments.
[0054] In the following examples and comparative examples, ionic conductivity test: X-ray diffractometer (XRD) was used for phase analysis: Nb instrument was Japan Rigaku XRD-MiniFlex600, and the line diffractometer used Cu-Kα line (including Kα2, ) as the ray source, the operating voltage during the test was 40 kV, the scanning speed was 10° / min, the step size was 0.02°, and the diffraction angle was 10°-80°; the electrolyte materials obtained by the reactions of the embodiments and the comparative examples were tested using AC impedance spectroscopy to obtain their ionic conductivity at room temperature, wherein a Swiss Metrohm PGSTAT302 electrochemical workstation was used with a test frequency range of 10 MHz to 1 Hz and a bias of 10 mV. 200 mg of the weighed oxychloride electrolyte material was pressed into a sheet using an Al2O3 sleeve mold with a diameter of 10 mm, and a pressure holding test was performed using an aluminum sheet as a blocking electrode.
[0055] In the following embodiments and comparative examples, all-solid-state battery preparation: Composite positive electrode preparation: The vacuum-dried high-nickel positive electrode material (Ni83, Ni89, Ni92) was placed in a glove box, and 0.8 g of positive electrode material and 0.2 g of oxychloride electrolyte material were taken in an agate mortar in a mass ratio of 8:2. They were manually ground and mixed to obtain a qualified composite positive electrode powder; Negative electrode preparation: In an ordinary environment, graphite: conductive carbon black (SP): carbon nanotubes (CNT): sodium carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95:1.0:0.5:1.2:1.8 were used as raw materials through a THINKY blender, and ultrapure water was used as a solvent to mix the negative electrode slurry evenly, and then the slurry was evenly coated on a copper foil with a thickness of 8 μm. After drying, rolling, slitting and die-cutting, qualified negative electrode sheets were obtained; in an argon glove box with a moisture and oxygen content of less than 0.1ppm, the prepared composite positive electrode powder, negative electrode sheets and sulfide electrolyte were pressed into an all-solid-state battery, including 33.8mg of composite positive electrode powder, 150mg of sulfide electrolyte and 27mg of negative electrode sheets.
[0056] In the following embodiments and comparative examples, the charge rate test is as follows: an all-solid-state battery containing an electrolyte material obtained by the reaction of the embodiment or comparative example is installed on a charge and discharge device at room temperature, and charged to 4.2V at a rate of 1 / 3C of the battery capacity, and then charged at a constant voltage of 4.2V until the current is less than 0.05C and the charge is cut off. After standing for 0.5h, the battery cell is discharged to 2.0V at a rate of 1C and allowed to stand for 30min. Subsequently, the discharge capacity is used as the 1C capacity standard, and a charge and discharge test is performed with a charge rate of 0.5C / 1C / 2C and a discharge rate of 0.33C. The test results are shown in Table 1, which is a table of room temperature rate charging results of all-solid-state batteries.
[0057] In some of the following examples and comparative examples, the discharge rate test is as follows: at room temperature, an all-solid-state battery obtained from the electrolyte material synthesized based on the example or comparative example is installed on a charging and discharging device and charged to 4.2V at a rate of 1 / 3C of the battery capacity, followed by constant voltage charging at 4.2V until the current is less than 0.05C and the charging is cut off. After the battery cell is allowed to stand for 0.5h, the battery is discharged to 2.0V at a rate of 1C. After standing for 0.5h, the battery is discharged as a 1C capacity standard with a charge rate of 0.33C and a discharge rate of 0.5C / 1C / 2C. The test results are shown in Table 2, which is a table of room temperature rate discharge results of all-solid-state batteries.
[0058] In the following examples, lithium hydroxide was subjected to vacuum drying pretreatment: the LiOH·H2O raw material was vacuum dried at 120°C in a vacuum drying oven using an enamel tray until the moisture content of the LiOH was <30 ppm.
[0059] Example 1
[0060] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0061] In the following examples, in a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.8360 g of LiOH raw material and 9.4301 g of NbCl5 were weighed according to a molar ratio of LiOH:NbCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g level. The inert gas in the ball mill was nitrogen, the ball milling balls had a diameter of 10 mm and were made of ZrO2. The mass ratio of the ball milling balls to the raw material was 25:1, the mass of the ball milling balls was 257 g, the ball milling speed was 250 rpm, and the ball milling time was 40 h. The reaction resulted in an oxychloride electrolyte material, LiNbOCl4, with a room temperature ionic conductivity of 8.55 mS / cm.
[0062] Example 2
[0063] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0064] In a nitrogen glove box with a moisture and oxygen content of less than 0.1ppm, 0.8360g of LiOH raw material and 9.4301g of NbCl5 were weighed according to the molar ratio of LiOH:NbCl5=1:1, and placed in a 500ml ZrO2 ball mill for 10g stage reaction. The inert gas in the ball mill is nitrogen, the ball milling balls have a diameter of 10mm and are made of ZrO2. The mass ratio of the ball milling balls to the raw materials is 10:1, the mass of the ball milling balls is 103g, the ball milling speed is 250rpm, and the ball milling time is 40h. The reaction obtains the oxychloride electrolyte material LiNbOCl4, whose room temperature ionic conductivity is 6.14mS / cm.
[0065] Example 3
[0066] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0067] In a nitrogen glove box with a moisture and oxygen content of less than 0.1ppm, 0.8360g of LiOH raw material and 9.4301g of NbCl5 were weighed according to the molar ratio of LiOH:NbCl5=1:1, and placed in a 500ml ZrO2 ball mill for 10g stage reaction. The inert gas in the ball mill is nitrogen, the ball milling balls have a diameter of 10mm and are made of ZrO2. The mass ratio of the ball milling balls to the raw materials is 15:1, the mass of the ball milling balls is 154g, the ball milling speed is 250rpm, and the ball milling time is 40h. The reaction obtains the oxychloride electrolyte material LiNbOCl4, whose room temperature ionic conductivity is 7.80mS / cm.
[0068] Example 4
[0069] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0070] In a nitrogen glove box with a moisture and oxygen content of less than 0.1ppm, 0.8360g of LiOH raw material and 9.4301g of NbCl5 were weighed according to the molar ratio of LiOH:NbCl5=1:1, and placed in a 500ml ZrO2 ball mill for 10g stage reaction. The inert gas in the ball mill is nitrogen, the ball milling balls have a diameter of 10mm and are made of ZrO2. The mass ratio of the ball milling balls to the raw materials is 35:1, the mass of the ball milling balls is 359g, the ball milling speed is 250rpm, and the ball milling time is 40h. The reaction obtains the oxychloride electrolyte material LiNbOCl4, whose room temperature ionic conductivity is 9.01mS / cm.
[0071] Example 5
[0072] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0073] In a nitrogen glove box with a moisture and oxygen content of less than 0.1ppm, 0.8360g of LiOH raw material and 9.4301g of NbCl5 were weighed according to the molar ratio of LiOH:NbCl5=1:1, and placed in a 500ml ZrO2 ball mill for 10g stage reaction. The inert gas in the ball mill is nitrogen, the ball milling balls have a diameter of 10mm and are made of ZrO2. The mass ratio of the ball milling balls to the raw materials is 45:1, the mass of the ball milling balls is 462g, the ball milling speed is 250rpm, and the ball milling time is 40h. The reaction obtains the oxychloride electrolyte material LiNbOCl4, whose room temperature ionic conductivity is 7.23mS / cm.
[0074] Example 6
[0075] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0076] In a nitrogen glove box with a moisture and oxygen content of less than 0.1ppm, 0.8360g of LiOH raw material and 9.4301g of NbCl5 were weighed according to the molar ratio of LiOH:NbCl5=1:1, and placed in a 500ml ZrO2 ball mill for 10g stage reaction. The inert gas in the ball mill is nitrogen, the ball milling balls have a diameter of 10mm and are made of ZrO2. The mass ratio of the ball milling balls to the raw materials is 35:1, the mass of the ball milling balls is 359g, the ball milling speed is 250rpm, and the ball milling time is 10h. The reaction obtains the oxychloride electrolyte material LiNbOCl4, whose room temperature ionic conductivity is 8.76mS / cm.
[0077] Example 7
[0078] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0079] In a nitrogen glove box with a moisture and oxygen content of less than 0.1ppm, 0.8360g of LiOH raw material and 9.4301g of NbCl5 were weighed according to the molar ratio of LiOH:NbCl5=1:1, and placed in a 500ml ZrO2 ball mill for 10g stage reaction. The inert gas in the ball mill is nitrogen, the ball milling balls have a diameter of 10mm and are made of ZrO2. The mass ratio of the ball milling balls to the raw materials is 35:1, the mass of the ball milling balls is 359g, the ball milling speed is 250rpm, and the ball milling time is 20h. The reaction obtains the oxychloride electrolyte material LiNbOCl4, whose room temperature ionic conductivity is 10.50mS / cm.
[0080] Example 8
[0081] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0082] In a nitrogen glove box with a moisture and oxygen content of less than 0.1ppm, 0.8360g of LiOH raw material and 9.4301g of NbCl5 were weighed according to the molar ratio of LiOH:NbCl5=1:1, and placed in a 500ml ZrO2 ball mill for 10g stage reaction. The inert gas in the ball mill is nitrogen, the ball milling balls have a diameter of 10mm and are made of ZrO2. The mass ratio of the ball milling balls to the raw materials is 35:1, the mass of the ball milling balls is 359g, the ball milling speed is 200rpm, and the ball milling time is 20h. The reaction obtains the oxychloride electrolyte material LiNbOCl4, whose room temperature ionic conductivity is 7.93mS / cm.
[0083] Example 9
[0084] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0085] In a nitrogen glove box with a moisture and oxygen content of less than 0.1ppm, 0.8360g of LiOH raw material and 9.4301g of NbCl5 were weighed according to the molar ratio of LiOH:NbCl5=1:1, and placed in a 500ml ZrO2 ball mill for 10g stage reaction. The inert gas in the ball mill is nitrogen, the ball milling balls have a diameter of 10mm and are made of ZrO2. The mass ratio of the ball milling balls to the raw materials is 35:1, the mass of the ball milling balls is 359g, the ball milling speed is 300rpm, and the ball milling time is 20h. The reaction obtains the oxychloride electrolyte material LiNbOCl4, whose room temperature ionic conductivity is 6.10mS / cm.
[0086] Example 10
[0087] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0088] In a nitrogen glove box with a moisture and oxygen content of less than 0.1ppm, 0.8360g of LiOH raw material and 9.4301g of NbCl5 were weighed according to the molar ratio of LiOH:NbCl5=1:1, and placed in a 500ml ZrO2 ball mill for 10g stage reaction. The inert gas in the ball mill is nitrogen, the ball milling balls have a diameter of 10mm and are made of ZrO2. The mass ratio of the ball milling balls to the raw materials is 35:1, the mass of the ball milling balls is 359g, the ball milling speed is 250rpm, and the ball milling time is 60h. The reaction obtains the oxychloride electrolyte material LiNbOCl4, whose room temperature ionic conductivity is 10.01mS / cm.
[0089] Example 11
[0090] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0091] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 25:1, the mass of the ball milling balls was 258 g, the ball milling speed was 250 rpm, and the ball milling time was 40 h. The reaction obtained the precursor LiTaOCl4, which was heat treated at 250°C for 2 h to obtain LiTaOCl4, whose room temperature ionic conductivity was 7.08 mS / cm.
[0092] Example 12
[0093] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0094] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 10:1, the mass of the ball milling balls was 103 g, the ball milling speed was 250 rpm, and the ball milling time was 40 h. The reaction obtained the precursor LiTaOCl4, which was heat treated at 250°C for 2 h to obtain LiTaOCl4, whose room temperature ionic conductivity was 8.14 mS / cm.
[0095] Example 13
[0096] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0097] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 40 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at 250°C for 2 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 10.43 mS / cm.
[0098] Example 14
[0099] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0100] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 35:1, the mass of the ball milling balls was 361 g, the ball milling speed was 250 rpm, and the ball milling time was 40 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at 250°C for 2 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 9.54 mS / cm.
[0101] Example 15
[0102] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0103] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 45:1, the mass of the ball milling balls was 464 g, the ball milling speed was 250 rpm, and the ball milling time was 40 h. LiTaOCl4 was reacted and heat treated at 250°C for 2 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 8.12 mS / cm.
[0104] Example 16
[0105] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0106] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 10 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at 250°C for 2 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 9.80 mS / cm.
[0107] Example 17
[0108] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0109] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 20 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at 250°C for 2 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 12.80 mS / cm.
[0110] Example 18
[0111] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0112] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 200 rpm, and the ball milling time was 20 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at 250°C for 2 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 8.11 mS / cm.
[0113] Example 19
[0114] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0115] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 300 rpm, and the ball milling time was 20 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at 250°C for 2 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 6.16 mS / cm.
[0116] Example 20
[0117] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0118] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for a 10 g scale reaction. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 60 h. The reaction produced LiTaOCl4, which was then heat treated at 250°C for 2 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 8.28 mS / cm.
[0119] Example 21
[0120] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0121] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to the molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for 10 g reaction. The inert gas in the ball mill was nitrogen, the ball milling balls had a diameter of 10 mm and were made of ZrO2. The mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 20 h. The reaction produced LiTaOCl4, whose room temperature ionic conductivity was 6.25 mS / cm.
[0122] Example 22
[0123] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0124] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 20 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at 350°C for 1 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 3.93 mS / cm.
[0125] Example 23
[0126] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0127] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 20 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at 300°C for 1 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 8.11 mS / cm.
[0128] Example 24
[0129] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0130] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 20 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at 250°C for 1 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 11.97 mS / cm.
[0131] Example 25
[0132] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0133] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 20 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was heat treated at 200°C for 1 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 10.15 mS / cm.
[0134] Example 26
[0135] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0136] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 20 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at a temperature of 150°C and a heat treatment time of 1 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 8.00 mS / cm.
[0137] Example 27
[0138] This example is used to illustrate the preparation method of the oxychloride electrolyte material and the oxychloride electrolyte material of the present invention.
[0139] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 0.6461 g of LiOH raw material and 9.6641 g of TaCl5 were weighed according to a molar ratio of LiOH:TaCl5=1:1, and placed in a 500 ml ZrO2 ball mill for reaction at a 10 g scale. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw material was 15:1, the mass of the ball milling balls was 155 g, the ball milling speed was 250 rpm, and the ball milling time was 20 h. LiTaOCl4 was reacted to obtain LiTaOCl4, which was then heat treated at 250°C for 0.5 h to obtain the final LiTaOCl4 with a room temperature ionic conductivity of 8.65 mS / cm.
[0140] Comparative Example 1
[0141] In a nitrogen glove box with a moisture and oxygen content of less than 0.1 ppm, 2.6744 g of LiCl and 7.3530 g of ZrCl4 raw materials were weighed according to the molar ratio of LiCl:ZrCl4=2:1 and placed in a 500 ml ZrO2 ball mill for a 10 g-scale reaction. The inert gas in the ball mill was nitrogen, the ball milling balls were 10 mm in diameter and made of ZrO2, the mass ratio of the ball milling balls to the raw materials was 30:1, the ball milling speed was 250 rpm, and the ball milling time was 40 h to obtain Li2ZrCl6, whose room temperature ionic conductivity was 0.24 mS / cm.
[0142] Comparative Example 2
[0143] Compared with Comparative Example 1, the difference is that 9.3988g of ZrCl4 and 0.6024g of Li2O are weighed according to the molar ratio of ZrCl4:Li2O=1:0.5 to obtain LiZrO 0.5 Cl4, its room temperature ionic conductivity is 1.26mS / cm.
[0144] Comparative Example 3
[0145] Compared with Comparative Example 1, the difference is that 1.7162g of LiCl, 7.0776g of ZrCl4, and 1.2097g of Li2O were weighed according to the molar ratio of LiCl: ZrCl4: Li2O = 1: 0.75: 1 to obtain Li3Zr 0.75 OCl4, its room temperature ionic conductivity is 2.57mS / cm.
[0146] Comparative Example 4
[0147] Compared with Comparative Example 1, the difference is that 3.0767g of LiCl, 5.6393g of ZrCl4, and 1.3081g of FeCl3 are weighed according to the molar ratio of LiCl: ZrCl4: FeCl3 = 2.25: 0.75: 0.25 to obtain LiCl 2.25 Zr 0.75 Fe 0.25 Cl6, its room temperature ionic conductivity is 1.76mS / cm.
[0148] It can be seen from the ionic conductivity test data that the ionic conductivity of LiNbOCl4 and LiTaOCl4 oxychloride electrolyte materials at room temperature is above 6mS / cm. The ionic conductivity of LiNbOCl4 oxychloride electrolyte material can reach up to 10.5mS / cm, and the ionic conductivity of LiTaOCl4 oxychloride electrolyte material can reach up to 12.8mS / cm. The comparative examples show that the ionic conductivity performance of LiTaOCl4 oxychloride electrolyte material is slightly better than that of LiNbOCl4 oxychloride electrolyte material. The comparative examples and comparative examples show that the ionic conductivity of LiMOCl4 (M = Nb, Ta) is much higher than that of Li2ZrCl6. In comparative examples 2-4, the ionic conductivity of the Zr-based halide electrolyte Li2ZrCl6 is improved after element doping modification, but it is still much lower than that of LiMOCl4 (M = Nb, Ta).
[0149] Table 1. Room temperature rate charging results of all-solid-state batteries
[0150] Example 0.33C rate 0.5C rate 1C rate 2C rate <![CDATA[Example 1 (LiNbOCl4)]]> 100% 99% 83% 74% <![CDATA[Example 2 (LiNbOCl4)]]> 100% 98% 75% 60% <![CDATA[Example 3 (LiNbOCl4)]]> 100% 99% 88% 71% <![CDATA[Example 4 (LiNbOCl4)]]> 100% 100% 94% 80% <![CDATA[Example 5 (LiNbOCl4)]]> 100% 99% 84% 72% <![CDATA[Example 6 (LiNbOCl4)]]> 100% 99% 83% 74% <![CDATA[Example 7 (LiNbOCl4)]]> 100% 100% 96% 81% <![CDATA[Example 8 (LiNbOCl4)]]> 100% 99% 85% 77% <![CDATA[Example 9 (LiNbOCl4)]]> 100% 99% 80% 65% <![CDATA[Example 10 (LiNbOCl4)]]> 100% 99% 88% 77% <![CDATA[Example 11 (LiTaOCl4)]]> 100% 99% 89% 77% <![CDATA[Example 12 (LiTaOCl4)]]> 100% 100% 89% 79% <![CDATA[Example 13 (LiTaOCl4)]]> 100% 100% 92% 82% <![CDATA[Example 14 (LiTaOCl4)]]> 100% 99% 89% 79% <![CDATA[Example 15 (LiTaOCl4)]]> 100% 99% 88% 76% <![CDATA[Example 16 (LiTaOCl4)]]> 100% 100% 93% 81% <![CDATA[Example 17 (LiTaOCl4)]]> 100% 100% 94% 83% <![CDATA[Example 18 (LiTaOCl4)]]> 100% 100% 89% 79% <![CDATA[Example 19 (LiTaOCl4)]]> 100% 99% 79% 60% <![CDATA[Example 20 (LiTaOCl4)]]> 100% 100% 92% 80% <![CDATA[Comparative Example 1 (Li2ZrCl6)]]> 100% 98% 78% 65% <![CDATA[Comparative Example 2 (LiZrO 0.5 Cl4)]]> 100% 99% 87% 75% <![CDATA[Comparative Example 3 (Li3Zr 0.75 OCl4)]]> 100% 100% 89% 79% <![CDATA[Comparative Example 4 (Li 2.25 Zr 0.75 Fe 0.25 Cl6)]]> 100% 99% 87% 75%
[0151] As can be seen from Table 1, Comparative Example 1 is a traditional halide electrolyte Li2ZrCl6, which has poor rate performance. After modification (Comparative Examples 2-4), the rate performance is improved, but still relatively low. LiNbOCl 4、 LiTaOCl4 has better charge rate performance. At a 2C rate, the capacity retention rate can be greater than 80%. The best charge capacity retention rate of LiNbOCl4 is 81%, and the best charge capacity retention rate of LiTaOCl4 is 83%.
[0152] Table 2. Room temperature rate discharge results of all-solid-state batteries
[0153]
[0154]
[0155] As can be seen in Table 2, the discharge capacity retention rate of Li2ZrCl6 in Comparative Example 1 is only 68%. After modification (Comparative Examples 2-4), the rate performance improves somewhat, but remains relatively low. LiNbOCl4 and LiTaOCl4 exhibit better discharge rate performance, achieving discharge capacity retention rates exceeding 80% at a 2C rate. The optimal discharge capacity retention rates for LiNbOCl4 are 85%, and for LiTaOCl4, 86%.
[0156] As can be seen from the above technical solutions of the embodiments of the present invention, the present invention discloses a method for preparing an oxychloride electrolyte material, the method comprising: providing raw materials; the raw materials comprising metal chloride and lithium hydroxide; reacting the metal chloride in the raw materials with lithium hydroxide under an inert gas atmosphere to obtain an oxychloride electrolyte material generated by the reaction. By using lithium hydroxide as the lithium raw material, it is cheap, which reduces the preparation cost. Hydrogen chloride is generated during the mixing preparation process, providing an acidic catalytic environment and shortening the preparation time. The prepared oxychloride electrolyte material introduces oxygen and chlorine elements. The oxychlorine framework structure composed of oxygen and chlorine elements is a significant flexible ion framework structure. The ion framework structure reduces the activation energy of lithium ion diffusion, thereby improving the room temperature ionic conductivity of the material, and further improving the room temperature rate performance of the all-solid-state battery based on the oxychloride electrolyte material.
[0157] The above description fully discloses the specific embodiments of the present invention. It should be noted that any modifications made by those skilled in the art to the specific embodiments of the present invention do not depart from the scope of the claims. Accordingly, the scope of the claims of the present invention is not limited solely to the foregoing specific embodiments.
Claims
1. A method for preparing an oxychloride electrolyte material, characterized in that: The method comprises: Providing raw materials; the raw materials include metal chloride and lithium hydroxide; Under an inert gas atmosphere, the metal chloride in the raw material reacts with the lithium hydroxide to obtain the oxychloride electrolyte material generated by the reaction.
2. The method for preparing an oxychloride electrolyte material according to claim 1, characterized in that: The metal chloride is one of NbCl5 and TaCl5.
3. The method for preparing an oxychloride electrolyte material according to claim 1, characterized in that: The provided raw materials include: Under an inert gas atmosphere, the metal chloride and the lithium hydroxide are weighed in an equimolar ratio.
4. The method for preparing an oxychloride electrolyte material according to claim 3, characterized in that: Before weighing the lithium hydroxide, the method further comprises: The previous lithium hydroxide is pre-treated by vacuum drying to obtain weighed lithium hydroxide, wherein the moisture value of the weighed lithium hydroxide is less than 30ppm.
5. The method for preparing an oxychloride electrolyte material according to claim 1, characterized in that: The step of reacting the metal chloride in the raw material with the lithium hydroxide to obtain the oxychloride electrolyte material generated by the reaction comprises: The metal chloride in the raw material is reacted with the lithium hydroxide by ball milling to obtain the oxychloride electrolyte material generated by the reaction.
6. The method for preparing an oxychloride electrolyte material according to claim 5, characterized in that: The mass ratio of the ball milling balls to the raw materials is (10-45):
1.
7. The method for preparing an oxychloride electrolyte material according to claim 5, characterized in that: The rotation speed of the ball mill is 200-300 rpm.
8. The method for preparing an oxychloride electrolyte material according to claim 5, characterized in that: The ball milling time is 10 to 60 hours.
9. A material, characterized in that An oxychloride electrolyte material prepared by the method for preparing an oxychloride electrolyte material according to any one of claims 1 to 8.
10. An all-solid-state battery, characterized in that: Comprising a material as described in claim 9.
Citation Information
Cited By
Oxygen halide solid electrolyte material and preparation method and application thereof
CN121377106A
An oxyhalide solid-state electrolyte material, and a preparation method and application thereof
CN121377106B